New Finding in KRAS Mutated Structure Detected in Colorectal Cancer CRC Tumors Causing Uncontrolled Cell Proliferation in Iraqi Patients - Subhi Ramadhan, Rehab; Najah Jabbar AL-Gafari, Rebah (International Journal of Engineering and Technology, 2018)
A total 200 tumor samples were collected from patients suffering from colorectal CRC at Al-Amal hospital. Their ages ranged from 40 â€“ 70 years old and distributed according to gender as 130 male and 70 female. We found that CRC was more common in male than female, and more frequent in elderly persons especially in age group of 61 â€“ 70 years old. From 12 specifically designed primers that were able to amplify KRAS gene in those patientsâ€™ blood samples, only 2 gave a specific band when tumor sample was used. Molecular analysis of the sequence obtained from those two primers showed the presence of 83 missense mutations in both of them, 20 in the first sequence were associated with pathogenic effect on KRAS gene, 3 frame shift, and 3 insertions, while in the second sequence obtained from primer PK2 4 frame shift mutations, and 4 insertions were identified. The impact finding is that in both sequences, open reading frames (ORFs) were developed that affected cell proliferation dramatically and produced truncated functionless proteins causing KRAS to cease control over cell cycle.Â Â